Evaluation of the impact of Diachasmimorpha longicaudata on Bactrocera invadens and five African fruit fly species - Mohamed, S.A.; Ekesi, S.; Hanna, R. (Wiley, 2008)
Diachasmimorpha longicaudata (Ashmead), a solitary koinobiont larval–prepupal endoparasitoid of fruit flies, was introduced into Kenya for testing and final release against the recently discovered invasive species, Bactrocera invadens Drew, Tsuruta and White in Africa. Laboratory experiments were conducted to determine host preference, host acceptability for oviposition and physiological suitability of B. invadens and five other indigenous tephritid fruit fly species –Ceratitis capitata (Wiedemann), Ceratitis cosyra (Walker), Ceratitis rosa Karsch, Ceratitis fasciventris (Bezzi) and Ceratitis anonae Graham – for the development of D. longicaudata. Females of D. longicaudata visited all host-larval patches, and were also attracted to these hosts at comparable levels. Acceptability, successful development of parasitoid progenies and their sex ratio varied widely across hosts. C. capitata yielded the highest parasitoid numbers whereas B. invadens was the only host that yielded a female-biased sex ratio. Larvae of B. invadens, C. rosa, C. fasciventris and C. anonae mounted differential immune reaction towards D. longicaudata eggs. Although, the parasitoid performed poorly on the target host B. invadens, it was able to form new association with C. cosyra and C. capitata. The prospect of using this parasitoid in biological control of African indigenous fruit flies is discussed.